2021
DOI: 10.1002/vms3.613
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Theileria equi, Babesia caballi, and Rickettsia in adult ticks from North of Xinjiang, China

Abstract: Background: Ticks in Xinjiang distribute widely and account for one third of China.Ticks can carry and transmit bacteria, virus, and parasite. However, the research of tickborne pathogens in Xinjiang is rather little.Objective: To understand the situation of hard tick carry Theileria equi, Babesia caballi and Rickettsia spp. of Zhaosu and Altay in Xinjiang. Methods:In this study, 119 tick samples were obtained from horses in Xinjiang, China, Ticks were identified morphologically to determine species and PCR wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Several genera of ticks, such as Haemaphysalis, Hyalomma, and Dermacentor, can carry and transmit diverse piroplasm pathogens by biting their hosts (Gong et al, 2005 ; Rothschild et al, 2013 ). These ticks are the predominant species in Xinjiang, China (Sheng et al, 2019 ), which has been reported to transmit T. equi and B. caballi (Zhang et al, 2021 ). The sampling sites as a major pastoral area of China were rich with vegetation cover and a diverse geographical environment, which are suitable for the growth and reproduction of ticks (Friedhoff et al., 1990 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several genera of ticks, such as Haemaphysalis, Hyalomma, and Dermacentor, can carry and transmit diverse piroplasm pathogens by biting their hosts (Gong et al, 2005 ; Rothschild et al, 2013 ). These ticks are the predominant species in Xinjiang, China (Sheng et al, 2019 ), which has been reported to transmit T. equi and B. caballi (Zhang et al, 2021 ). The sampling sites as a major pastoral area of China were rich with vegetation cover and a diverse geographical environment, which are suitable for the growth and reproduction of ticks (Friedhoff et al., 1990 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ]. In China, some molecular and serological investigations targeting B. caballi have been carried out, reporting its presence in multiple provinces including Xinjiang, Jilin, and Gansu [ 19 21 ]. Although reports on B. caballi is common, further analysis such as genotyping has been rare.…”
Section: Discussionmentioning
confidence: 99%